Impact of climate change on rice production - Gangaraju Subramanyam (Department of agricultural meteorology, College of horticulture, 2015)
The impacts of climate change on agriculture are global concerns and for that matter India, where agriculture sector alone represents 23 per cent of India’s Gross National Product (GNP) and the livelihood of nearly 70% of the population is exposed to a great danger, as the country is one of the most vulnerable countries to climate change. Climatic changes are already exerting a considerable drag on yield growth (Lobell et al., 2011). Future impacts of climate change on rice yield in India would likely be larger than the historical ones (Auffhammer et al., 2012). Objectives of the study were development of crop weather relationships for the selected rice varieties and assessment of possible change in yield due to climate change. The studies were conducted during 2014-15 at RARS, Pattambi in two varieties (Aathira and Vaisakh) with nine dates of planting. The results of the study showed the effect of weather parameters on biometric characters varied significantly with variety and time of planting. Both the varieties recorded the maximum plant height (Aathira is 133 cm and Vaisakh is 145.33 cm) when planted on June 1st and maximum LAI during June 15th. The highest grain yield of variety Vaisakh was recorded by the crop planted on January 1st (6.30 t ha-1). Whereas in Aathira crop planted on Oct 30th (5.86 t ha-1) recorded the highest yield. In both the varieties minimum temperature above 24.0°C in the panicle initiation to flowering stage has reduced the yields. Maximum temperature above 32.0°C during tillering stage will negatively influence the biomass accumulation. Multiple Regression equations were developed for predicting grain yield, leaf area index and duration. DSSAT model was validated and it was given good RMSE values for both the varieties (Aathira 515.6 kg ha-1, Vaisakh 377.75 kg ha-1). The simulation analysis as per the projected climatic scenarios for the periods 2030s, 2050s and 2080s indicate that among the two varieties, variety Aathira will perform better in the first crop season. Vaisakh, an upland variety, tolerant to temperature and drought, the performance is better under third crop season. The most alarming finding of the study is the huge reduction in yield during the second crop season, which is considered as the major rice growing season of Kerala. In RCP 4.5, which is the most likely scenario for India, the yield reduction will be 35 per cent, 38 per cent and 43 per cent during 2030s, 2050s and 2080s respectively in case of variety Aathira, the yield reduction will be 21 per cent, 40 per cent and 47 per cent during 2030s, 2050s and 2080s respectively for Vaisakh, during the second crop season.